The Appropriation of Biomedicine in Southeast Asia - Meriem M’zoughi (Université de Provence, 2021)
From surgical techniques to pharmaceutical treatments, included biological or clinical sciences: what are the specificities and contemporary realities of biomedicine in Southeast Asia? The diversity of its forms invites us to think about the situated character of knowledge and practices that medicalize and transform bodies. This issue examines the dimensions of care when it is produced by actors who mobilize and appropriate the conceptual and empirical tools of Western scientific medicine. It is dealing with providing care for the elderly in North Sulawesi, caregivers of children living with HIV/AIDS in Laos, the healing of a brain tumor among the Dayak Benuaq in East Kalimantan, Cambodian oncologists practices, as well as obstetric violence in Indonesia and Cambodia. All the contributions allow us to analyze how treatment and care are provided in hospitals, private clinics, and health centers to question, more broadly, what it means to be a doctor, a patient, a caregiver or a woman in this region of the world. Far from being exhaustive, these approaches contribute to understanding how biomedicine interferes in the daily life of patients and families by analyzing its current forms, what imaginary and values it carries today in Southeast Asia?